Coordinated Role of Toll-Like Receptor-3 and Retinoic Acid-Inducible Gene-I in the Innate Response of Bovine Endometrial Cells to Virus - Carneiro, Luisa C.; Bedford, Carmen; Jacca, Sarah; Rosamilia, Alfonso; de Lima, Vera F.; Donofrio, Gaetano; Sheldon, I. Martin; Cronin, James G. (Frontiers in Immunology, 2017)
Bovine herpesvirus-4 (BoHV-4) and bovine viral diarrhea virus (BVDV) infect the uterus of cattle, often resulting in reduced fertility, or abortion of the fetus, respectively. Here, exposure of primary bovine endometrial cells to BoHV-4 or BVDV modulated the production of inflammatory mediators. Viral pathogen-associated molecular patterns (PAMPs) are detected via pattern-recognition receptors (PRRs). However, the relative contribution of specific PRRs to innate immunity, during viral infection of the uterus, is unclear. Endometrial epithelial and stromal cells constitutively express the PRR Toll-like receptor (TLR)-3, but, the status of retinoic acid-inducible gene I (RIG-I), a sensor of cytosolic nucleic acids, is unknown. Primary endometrial epithelial and stromal cells had low expression of RIG-I, which was increased in stromal cells after 12 h transfection with the TLR3 ligand Poly(I:C), a synthetic analog of double-stranded RNA. Furthermore, short interfering RNA targeting TLR3, or interferon (IFN) regulatory transcription factor 3, an inducer of type I IFN transcription, reduced Poly(I:C)-induced RIG-I protein expression and reduced inflammatory mediator secretion from stromal cells. We conclude that antiviral defense of endometrial stromal cells requires coordinated recognition of PAMPs, initially via TLR3 and later via inducible RIG-I.